Pelajaran Pendidikan Karakter yang Bisa Diambil dari Kehidupan dan Karier Cristiano Ronaldo sebagai Superstar Sepak Bola - Robingun Suyud El Syam; Aryadi Nursantoso; Danang Isworo (Journal of New Trends in Sciences, 2025)
The purpose of this study is to reveal the character education values of the superstar Cristiano Ronaldo, which have not been studied in depth before. The character research was selected with literature sources, and analyzed qualitatively. The discussion and analysis resulted in findings that Cristiano Ronaldo has several superior characters, namely: religious, honest, competitive, self-confident, professional, high work ethic, disciplined, love for the country, appreciate achievement, communicative, care for the environment, care for society, and responsibility. These character values make him a superstar who stands out both on and off the field. His religious devotion, honesty, and sense of responsibility reflect strong moral foundations, setting him as a role model for aspiring athletes and individuals seeking success. Ronaldo's competitive spirit and high self-confidence have helped him achieve excellence on the field, while his professional attitude and exceptional work ethic highlight the importance of dedication and perseverance in achieving success. Furthermore, his discipline in training and love for his country portray a deep commitment not only to his career but also to his community and country. Additionally, Ronaldo's appreciation for achievement, communicative nature, and care for the environment demonstrate that his character extends beyond personal success, as he values teamwork and the well-being of others. His contribution to various charitable causes and societal issues further establishes his role as a responsible individual who uses his fame and fortune for the betterment of society. These character values make him an ideal role model, both in the world of sports and in broader society. We recommend Cristiano Ronaldo's character values as a role model for those who hope for a successful career, and inspiration for the practice of Islamic education values, as they encompass integrity, hard work, and social responsibility.